LONG-TERM RESULTS OF THE USE OF STENTS MADE OF NITI WITH THE STRICTURES OF THE URETERS OF VARIOUS LOCATION ‒ OWN EXPERIENCE - S. Y. Yarovoy; V. A. Maximov; E. V. Medvedev; Z. O. Achba; A. B. Shouа; S. V. Markaryan (Вестник урологии)
Long-term results of the use of stents made of niti with the strictures of the ureters of various localization-own experience of 6 years offollow-up. For the period from April 2009 to March 2011 completed installation of 20 stents of Nickel titanium in 15 patients. Of them 6 women, 9 men from 28 to 80 years, mean age was 54 years. The stents used included with the delivery device produced by Meath Russia. Of the 15 patients 5 patients (33.3%), the stent was removed due to complications, the remaining 10 patients (66,6%) are observed to the present time with a stent without complications.The study conclusions:1. The study of remote results of treatment of patients with obstructions of the ureter through the stent made of niti showed a positive result in 66% of cases, indicating the effectiveness of this minimally invasive method of treatment.2. Installation stents of Nickel titanium in the field of vesicoureteral anastomosis after the TOUR can be a method of temporary extended drainage, which requires careful clinical observation and does not constitutea radical method of treatment.3. The stent for the purpose of removal of obstruction caused by the deviation of the ureter may lead to migration of the stent and requires further research in this direction.4. When established strictures of ureteral calculi of any localization stent made of niti is the method of choice of effective and minimally invasive treatment, especially in somatically complicated patients.